The Role of Westernization in the Changing African Family Structures: A Systematic Literature Review - Andeskebtso Yohanna Adaki (Humanities, Society, and Community, 2023)
As African societies continue to experience rapid social and economic transformations, traditional family systems are undergoing significant shifts, giving way to new forms and dynamics, with the diffusion of Western cultural values, ideologies, and practices being identified as a major catalyst in reshaping family structures across the continent. This paper explored the impact of Westernization on the African traditional family, focusing on causes, dynamics, and effects. It explored the dimensions of Westernization and its impact on family life in Africa, encompassing areas such as marriage patterns, household sizes, gender roles, divorce rates, intergenerational relationships, and the dynamics of kinship networks. Utilizing a systematic literature review (SLR) methodology, this research aggregated and synthesized insights from an array of scholarly works spanning cultural sociology, globalization studies, and African family dynamics and captured how Western ideals, such as individualism, gender equality, and nuclear family models, have both challenged and coexisted with traditional norms, often leading to a shift from traditional arranged marriages to more self-centred decisions like dating and cohabitation. The paper argued further that the influence of Westernization on family structures in Africa is multidimensional, with both positive and negative outcomes. As African societies navigate the complexities of cultural preservation and adaptation, balancing traditional values and Western influences is crucial for maintaining harmonious family dynamics across generations. The paper concluded by emphasizing the need for informed approaches to understanding the impact of Westernization on African family structures.